Looking at Financial Performance, Analysis of its Effect on Share Prices - Surono, Yunan; Simarmata, Jonner; Riady, Yasir; Yati, Yati; Pratiwi, Heni; Hutabarat, Zuhri Saputra; Sembiring, Benar (Information Technology and Science (ITScience), 2024)
This study aims to determine and analyze the effect of financial performance on stock prices in pharmaceutical sub-sector companies on the Indonesia Stock Exchange for the period 2014 – 2023. This study uses financial performance as an independent variable with indicators of Current Ratio (CR), Quick Ratio (QR), Cash Ratio (CashR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Fixed Asset Turn Over (FATO), Inventory Turn Over (ITO), Total Asset Turn Over (TATO), Gross Profit Margin (GPM), Net Profit Margin (NPM) and Return On Equity (ROE). Stock price as a variable is tied to the stock price indicator (HS). Data and facts obtained from the issuer's financial statements, stock prices and financial performance have considerable and significant differences in the study period. The analysis tool uses the Smart Partial Least Square (PLS) 3.0 software program. The results showed that financial performance variables with FATO and TATO indicators affect stock price variables, while other financial performance indicators, namely CR, CashR, DAR, DER, GPM, ITO, GPM, ITO, NPM, QR and ROE are not able to construct financial performance variables.